Efficient Generation of Microwave Plasmonic Vortices via a Single Deep‐Subwavelength Meta‐Particle. Issue 9 (13th June 2018) - Su, Hai; Shen, Xiaopeng; Su, Guangxu; Li, Lin; Ding, Jianping; Liu, Fanxin; Zhan, Peng; Liu, Yongmin; Wang, Zhenlin
Abstract: Light beams carrying orbital angular momentum (OAM) in the form of optical vortices have attracted great interest due to their capability for providing a new dimension and approach to manipulate light–matter interactions. Recently, plasmonics has offered efficient ways to focus vortex beams beyond the diffraction limit. However, unlike in the visible and near‐infrared regime, it is still a big challenge to realize plasmonic vortices at far‐infrared and even longer wavelengths. An effective strategy to create deep‐subwavelength near‐field electromagnetic (EM) vortices operating in the low frequency region is proposed. Taking advantage of the asymmetric spatial distribution of EM field supported by a metallic comb‐shaped waveguide, plasmonic vortex modes that are strongly confined in a well‐designed deep‐subwavelength meta‐particle with desired topological charges can be excited. Such unique phenomena are confirmed by the microwave experiments. An equivalent physical model backed up by the numerical simulations is performed to reveal the underlying mechanism of the plasmonic vortex generation. This spoof‐plasmon assisted focusing of EM waves with OAM may find potentials for functional integrated elements and devices operating in the microwave, terahertz, and even far‐infrared regions. Abstract : Plasmonics offers efficient ways to focus vortex beams beyond the diffraction limit. However, the effective excitation of surface plasmons is limited to visible and near‐infrared frequencies. Here, an novel strategy is proposed to overcome this limitation and generate deep‐subwavelength plasmonics‐like vortices, which may find applications in integrated elements and devices operating in the microwave or terahertz regions.